"Push-no-pull" porphyrins for second harmonic generation imaging - Lopez-Duarte, I; Reeve, J; Reeve, J; Perez-Moreno, J; Perez-Moreno, J; Boczarow, I; Boczarow, I; Depotter, G; Depotter, G; Fleischhauer, J; Fleischhauer, J; Clays, K; et al. (2013)
The established approach to design a molecule with strong second-order nonlinear optical (NLO) activity is to connect an electron-donor to an electron-acceptor via a π-conjugated bridge, to generate push-pull system. Surprisingly, we have found that dyes with large first hyperpolarizabilities, and which exhibit strong second harmonic generation (SHG), can be created just by attaching an electron-donor to a porphyrin. The free-base porphyrin core is sufficiently electron-deficient that the hyperpolarizability does not increase on addition of a pyridinium electron-acceptor. © 2013 The Royal Society of Chemistry.